Evaluation of nursing records in the water balance of patients in intensive care unit - Elizabeth Mesquita Melo, Isabel Cristina Fernandes Sales, Diva Teixeira de Almeida, Francisca Elisângela Teixeira Lima, Joelna Eline Gomes Lacerda de Freitas Veras, Rita Mônica Borges Studart (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/reufpi.v3i4.2092